RFID System in Library: Application of Library Management System - Bansal, Vipul (IJRDO- Journal of Educational Research, 2018)
Radio Frequency Identification (RFID) is one of the exciting technology that revolutionized the working practices by increasing efficiencies and improving profitability. Deployment of RFID system is rapidly growing and has the potential to affect many different libraries. The article provides details about RFID, its components, how it works, and its usage in library.